2014
DOI: 10.1212/wnl.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 deficiency in herpes simplex encephalitis

Abstract: Objective: To determine the proportion of children with herpes simplex encephalitis (HSE) displaying TLR3 deficiency, the extent of TLR3 allelic heterogeneity, and the specific clinical features of TLR3 deficiency. Methods:We determined the sequence of all exons of TLR3 in 110 of the 120 patients with HSE enrolled in our study who do not carry any of the previously described HSE-predisposing mutations of TLR3 pathway genes (TLR3, UNC93B1, TRIF, TRAF3, and TBK1). All the new mutant TLR3 alleles detected were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
121
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 34 publications
8
121
0
6
Order By: Relevance
“…A recent study revealed that the polymorphism of TLR3 gene plays a role in the development of clinical tick-borne encephalitis in the Lithuanian population and may be associated with disease severity (Mickienė et al, 2014). Another recently published study also suggested that abnormalities of central nervous system-intrinsic TLR3 immunity might be important in the pathogenesis of herpes simplex encephalitis during the course of primary herpes simplex encephalitis 1 infection (Lim et al, 2014). In an isolated patient with influenza-associated encephalopathy, authors detected a novel missense mutation (F303S) in TLR3 gene (Hidaka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the polymorphism of TLR3 gene plays a role in the development of clinical tick-borne encephalitis in the Lithuanian population and may be associated with disease severity (Mickienė et al, 2014). Another recently published study also suggested that abnormalities of central nervous system-intrinsic TLR3 immunity might be important in the pathogenesis of herpes simplex encephalitis during the course of primary herpes simplex encephalitis 1 infection (Lim et al, 2014). In an isolated patient with influenza-associated encephalopathy, authors detected a novel missense mutation (F303S) in TLR3 gene (Hidaka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A striking example is that mutations in genes controlling Toll-like receptor (TLR) 3-dependent type I and III IFN-mediated immunity confer susceptibility to herpes simplex encephalitis (HSE) (17)(18)(19)(20)(21)(22). Notably, these genetic defects often appear to display incomplete penetrance, in which case they can be designated as monogenic but not Mendelian (18,20,23). Common to the identified genetic defects in the TLR3 pathway is that they lead to reduced type I and III IFN induction in patients cells after HSV-1 infection or stimulation through the TLR3 pathway ex vivo.…”
Section: Identification Of Heterozygous Mutations In Polr3a and Polr3mentioning
confidence: 99%
“…Мутации в этом гене ассоциированы с риском развития энце-фалита, вызываемого вирусом простого герпеса. Было показано, что рецидивы энцефалита возни-кают у пациентов с дефектом TLR3 значительно чаще, чем обычно [1,7,12]. Данные о функцио-нальной значимости выявленного варианта отсут-ствуют, однако in silico предиктивные программы (PolyPhen2, SIFT, MutationTaster) расценивают его как патогенный.…”
Section: данные лабораторных и инструментальных исследованийunclassified
“…TLR3-зависимая индукция ИФН-α/β или ИФН-λ является критической для защиты центральной нервной системы против вируса простого герпеса [10]. TLR3-сигнальный путь включает целый ряд молекул (TLR3, UNC93B1, TRIF, TRAF3, and TBK1), дефект генов которых ассоциирован с риском раз-вития герпетического энцефалита [7]. По резуль-татам исследования H.K.…”
unclassified